The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1021/jacs.7b02869
|View full text |Cite
|
Sign up to set email alerts
|

Ultrafast Spectroscopy Reveals Electron-Transfer Cascade That Improves Hydrogen Evolution with Carbon Nitride Photocatalysts

Abstract: Solar hydrogen generation from water represents a compelling component of a future sustainable energy portfolio. Recently, chemically robust heptazine-based polymers known as graphitic carbon nitrides (g-CN) have emerged as promising photocatalysts for hydrogen evolution using visible light while withstanding harsh chemical environments. However, since g-CN electron-transfer dynamics are poorly understood, rational design rules for improving activity remain unclear. Here, we use visible and near-infrared femto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
190
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 220 publications
(212 citation statements)
references
References 89 publications
20
190
2
Order By: Relevance
“…The XRD patterns of g-C 3 N 4 showed ap eak at 27.78,w hich indicated ad ecreased galleryd istance between the basic sheets in the g-C 3 N 4 nanosheets ( Figure S2). [14,15,36,38] These agree well with the significant increase in volume during the exfoliation of bulk g-C 3 N 4 to g-C 3 N 4 nanosheets ( Figure S3). Then, acobalt(II) phenanthroline complex was impregnatedo ng -C 3 N 4 nanosheets or bulk g-C 3 N 4 ,f ollowed by pyrolysis under an itrogen atmosphere.…”
Section: Resultssupporting
confidence: 74%
See 1 more Smart Citation
“…The XRD patterns of g-C 3 N 4 showed ap eak at 27.78,w hich indicated ad ecreased galleryd istance between the basic sheets in the g-C 3 N 4 nanosheets ( Figure S2). [14,15,36,38] These agree well with the significant increase in volume during the exfoliation of bulk g-C 3 N 4 to g-C 3 N 4 nanosheets ( Figure S3). Then, acobalt(II) phenanthroline complex was impregnatedo ng -C 3 N 4 nanosheets or bulk g-C 3 N 4 ,f ollowed by pyrolysis under an itrogen atmosphere.…”
Section: Resultssupporting
confidence: 74%
“…Compared with bulk g‐C 3 N 4 , the FT‐IR peaks of g‐C 3 N 4 in the region from 900 to 1800 cm −1 that were attributed to either trigonal C‐N(‐C)‐C or bridging C‐NH‐C units became sharper, probably due to the more ordered packing of hydrogen‐bond cohered long strands of polymeric melon units survived after thermal oxidation etching of bulk g‐C 3 N 4 (Figure S1). The XRD patterns of g‐C 3 N 4 showed a peak at 27.7°, which indicated a decreased gallery distance between the basic sheets in the g‐C 3 N 4 nanosheets (Figure S2) . These agree well with the significant increase in volume during the exfoliation of bulk g‐C 3 N 4 to g‐C 3 N 4 nanosheets (Figure S3).…”
Section: Resultssupporting
confidence: 73%
“…The partial exfoliation of FS-COF may also contribute. 10,44 The higher BET surface area of 1288 m 2 g -1 for FS-COF versus 919 m 2 g -1 for TP-COF might also enhance the availabliity of photogenerated charges for water reduction.…”
Section: Photocatalysis Experimentsmentioning
confidence: 99%
“…In a considerable range of laser power, we found that the decay dynamics of the induced TA signal keeps unchanged, which is obviously different from the previously reported no-geminate charge recombination. [25][26][27] Figure 3b shows the time-resolved kinetic curves, in which the temporal evolution of the 600 nm signal amplitude decreases with probe time. The carrier kinetic process can be divided into fast component (τ2 = 34.6 ps) and long lifetime channel (τ3 = 1.8 ns).…”
Section: Here Unprecedented Light-induced Switching Of Magnetism Is Rmentioning
confidence: 99%